(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2023)
The objective of this research is to evaluate the effectiveness of a functional training intervention on body composition in a group of 102 students aged 10 to 13 years old from the commune of Teno, Curicó province, Maule region. In the first instance, the anthropometric measurements of the students were evaluated: weight, height, waist and hip index, then a six-week functional training plan was applied, which was carried out during the Physical Education and Health class (two hours a week). The sessions were organized to work different muscle groups, with intervals of four minutes of execution of an exercise, for one minute of rest, increasing the intensity of the exercises each week. Once the intervention was completed, anthropometric measurements were reevaluated to determine the effectiveness of the intervention on the body composition of the students. The results showed that, after the intervention, their anthropometric measurements increased, except for waist circumference. It is concluded that a six-week functional training intervention in the Physical Education class is not effective in improving all the components of body composition measured. It is suggested to increase the weeks of application of functional training, as well as to increase its frequency to at least three times per week, in order to obtain significant improvements in the individuals.